Electrophysiological identification of nonrecurrent laryngeal nerves. (15th November 2016) - Kandil, Emad; Anwar, Muhammad A.; Bamford, Jeremy; Aslam, Rizwan; Randolph, Gregory W.
Abstract : Objectives/Hypothesis: The nonrecurrent laryngeal nerve (NRLN) is a common anatomic variation of the right recurrent laryngeal nerve (RLN), which has been associated with an increased risk of injury during thyroid and parathyroid surgery. We suggest that early successful identification using intraoperative nerve monitoring (IONM) and preservation of this variant will help the surgeon to avoid injury to this nerve. Our objective was to examine the electrophysiological parameters of the NRLN and the efficacy of IONM for successful identification of the NRLN. Study Design: Retrospective database analysis. Methods: This is a retrospective study of a prospectively collected database of all patients who underwent thyroid and parathyroid surgeries by a single surgeon at a tertiary care center over 3 years (n = 481). Patients' demographic data and operative reports, including the IONM reports, were reviewed. Average stimulation thresholds with resulting amplitudes and latencies were compared. Preoperative and postoperative laryngoscopy were performed in all cases. Results: We identified 15 NRLNs (2.2%) in a total 682 laryngeal nerves. No left‐sided NRLNs were observed. The average right vagus latency in the NRLN group was shorter than that of the RLN group (2.40 ms ± 0.49 ms vs. 3.43 ms ± 1.03 ms; P < .001). No statistically significant difference was observed between the initial amplitudes of the right vagus nerves in the two groups (713.67 μV ± 208.71 μV vs. 816.22 μV ± 470.45 μV; P = .14). All NRLN cases exhibited normal functioning of vocal cords on postoperative laryngoscopy. Conclusions: IONM is highly effective in the identification of the NRLN. Right vagus nerve latency in the NRLN group was found to be significantly shorter than in the RLN group. Early identification of the NRLN allowed cautious preservation of the NRLN, resulting in excellent postoperative outcomes. The rate of NRLN identification may be improved by routine use of IONM. Level of Evidence: 4 Laryngoscope, 127:2189–2193, 2017